Household debt and crises of confidence - Thomas Hintermaier; Winfried Koeniger (Goethe University Frankfurt, Center for Financial Studies (CFS), 2015)
We show that the size of collateralized household debt determines an economy's vulnerability to crises of confidence. The house price feeds back on itself by contributing to a liquidity effect, which operates through the value of housing in a collateral constraint. Over a specific range of debt levels this liquidity feedback effect is strong enough to give rise to multiplicity of house prices. In a dynamic setup, we conceptualize confidence as a realization of rationally entertainable belief-weightings of multiple future prices. This delivers debt-level-dependent bounds on the extent to which confidence may drive house prices and aggregate consumption.
urn:nbn:de:hebis:30:3-386603
Keywords: E21; E32; D91; 330; Household debt; Consumer confidence; Collateral constraints; Multiple equilibria